Lipopolysaccharide-Induced Dephosphorylation of AMPK-Activated Protein Kinase Potentiates Inflammatory Injury via Repression of ULK1-Dependent Autophagy - Fan, Kerui; Lin, Ling; Ai, Qing; Wan, Jingyuan; Dai, Jie; Liu, Gang; Tang, Li; Yang, Yongqiang; Ge, Pu; Jiang, Rong; Zhang, Li (Frontiers in Immunology, 2018)
AMP-activated protein kinase (AMPK) is a crucial metabolic regulator with profound modulatory activities on inflammation. Although the anti-inflammatory benefits of AMPK activators were well-documented in experimental studies, the pathological significance of endogenous AMPK in inflammatory disorders largely remains unknown. The present study investigated the phosphorylation status of endogenous AMPK and the potential roles of AMPK in mice with lipopolysaccharide (LPS)-induced lethal inflammation. The results indicated that LPS dose-dependently decreased the phosphorylation level of AMPK and its target protein acetyl-CoA carboxylase (ACC). Reactivation of AMPK with the AMPK activator A-769662 suppressed LPS-induced elevation of interleukin 6 (IL-6), alleviated histological abnormalities in lung and improved the survival of LPS-challenged mice. Treatment with A-769662 restored LPS-induced suppression of autophagy, inhibition of autophagy by 3-MA reversed the beneficial effects of A-769662. Treatment with A-769662 suppressed LPS-induced activation of mammalian target of rapamycin (mTOR), co-administration of mTOR activator abolished the beneficial effects of A-769662 and the suppressive effects of A-769662 on uncoordinated-51-like kinase 1 (ULK1) phosphorylation. Inhibition of ULK1 removed the beneficial effects of A-769662. These data indicated that LPS-induced dephosphorylation of AMPK could result in weakened inhibition of mTOR and repression of ULK1-dependent autophagy, which might potentiate the development of LPS-induced inflammatory injury. These data suggest that pharmacological restoration of AMPK activation might be a beneficial approach for the intervention of inflammatory disorders.